Characteristics of hospital admissions for pneumonia in HIV-positive individuals in Winnipeg, Manitoba: a cross-sectional retrospective analysis. (February 2018) - van Gaalen, S; Duff, Michael; Arroyave, Luisa F; Rueda, Zulma Vanessa; Kasper, Ken; Keynan, Y
Lung infection in human immunodeficiency virus (HIV)-positive individuals remains an important cause of morbidity and mortality, even in the current antiretroviral therapy era. Pneumonia is the most common cause of admission in HIV-positive individuals in our centre as reported in a previously published study. The objective of this retrospective observational study was to further characterize these admissions, with respect to index of disease severity at presentation, organisms identified, and investigations pursued including bronchoalveolar lavage (BAL). There were 123 unique patients accounting for a total of 209 admissions from 2005 to 2015. An organism was isolated in only 33% of all admissions (68/209). The most common organism was Pneumocystis jirovecii with a frequency of 29% of all admissions. Eighty-seven percent of presentations were mild, and 13% were moderate by CURB-65 criteria. A total of 39 BALs were performed, of which 27 yielded an organism (69%). Considering the burden of disease, low diagnostic yield of the current diagnostic strategy and increased morbidity and mortality caused by pneumonia in HIV-positive individuals, further methods are needed to more accurately target therapy. The preponderance of mild disease in this study suggests that better diagnostic tests may identify individuals that can be candidates for outpatient therapy.